2005
DOI: 10.1086/429327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 516G>T Polymorphisms at the Gene Encoding the CYP450-2B6 Isoenzyme on Efavirenz Plasma Concentrations in HIV-Infected Subjects

Abstract: We examined 516G>T polymorphisms at the gene encoding the cytochrome P450 in 100 human immunodeficiency virus-positive subjects who were receiving efavirenz (EFV). Elevated plasma EFV concentrations were found in 40% of subjects with the polymorphic homozygous genotype and 19% of subjects with the heterozygous genotype. Conversely, 20% of subjects with the wild-type genotype had subtherapeutic concentrations of EFV. CYP2B6-516 genotyping may help to identify subjects who have plasma EFV concentrations that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(124 citation statements)
references
References 12 publications
9
113
1
1
Order By: Relevance
“…Several studies [8][9][10][11][12][13][14] reported an association between the CYP2B6 G516T and A785G single nucleotide polymorphisms (SNPs) and the rate of plasma clearance of efavirenz and occurrence of related ADRs.…”
Section: Cyp2b6mentioning
confidence: 99%
“…Several studies [8][9][10][11][12][13][14] reported an association between the CYP2B6 G516T and A785G single nucleotide polymorphisms (SNPs) and the rate of plasma clearance of efavirenz and occurrence of related ADRs.…”
Section: Cyp2b6mentioning
confidence: 99%
“…Efavirenz-Several studies have identified a relationship between CYP2B6-G516T gene polymorphisms and plasma EFV pharmacokinetics in HIV-infected adults [13][14][15][16][17][18][19][20] and children [21] (Table 1). All available data have shown that the subjects with the CYP2B6-516-T/T genotype (homozygous variants) have consistently higher EFV concentrations compared to those with the CYP2B6-516-G/T (heterozygous variant) and G/ G genotype (wild type).…”
Section: Cyp2b6 Genotypes and Nnrti Pharmacokineticsmentioning
confidence: 99%
“…All available data have shown that the subjects with the CYP2B6-516-T/T genotype (homozygous variants) have consistently higher EFV concentrations compared to those with the CYP2B6-516-G/T (heterozygous variant) and G/ G genotype (wild type). Additional research also identified differences in EFV pharmacokinetics in subjects with the CYP2B6-516-G/T and those with the CYP2B6-516-G/ G genotypes [14,16,19,20].…”
Section: Cyp2b6 Genotypes and Nnrti Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, studies have also been done in African populations to evaluate the clinical implications of the CYP2B6*6 allele in the use of efavirenz [15][16][17][18], and nevirapine [19][20][21]. CYP2B6*6 has been associated with higher efavirenz plasma concentrations due to lower clearance rates, which may lead to CNS side effects [22,23].…”
Section: Introductionmentioning
confidence: 99%